Synchronized Phasor Measurements and Their Applications - Phadke, A.G; Thorp, J.S (Power Electronics and Power Systems, 2008)
Synchronized Phasor Measurement and Their Applications presents the historical development of the synchronized phasor measurement technology, which is the most accurate wide area measurements (WAMS) technology for power systems, and points the path for the applications of these measurements to be realized in coming years. The synchronized phasor measurement concept was introduced by the authors about 25 years ago and has been developing at a steady pace through the research of the authors as well as their colleagues throughout the world. It is now a mature technology with products being offered by leading manufacturers of electric power equipment. Electric Power Systems are an essential infrastructure of modern society and have been characterized as the largest man-made machines. Catastrophic failures of power systems - popularly known as blackouts - occur infrequently, but when they occur they cause great disruption to the fabric of industrial societies. In recent years, it has become evident that precise measurements of power systems' state in real time is a very important tool for managing the operation of power systems, as well as mitigating some of the effects of catastrophic failures. It has been well recognized by experts that synchronized phasor measurements offer the most direct and accurate tool for determining the state of the power system. Synchronized Phasor Measurement and Their Applications serves as a source for serious researchers and graduate students in universities and industrial organizations.